ARTIFICIAL INTELLIGENCE AND ITS RELATION WITH MANAGEMENT & CUSTOMER SUPPORT SERVICES - Ketkibhabra, (International Journal of Psychosocial Rehabilitation, 2020)
The coming era is the era of robotics and such robotics are a result of AI. Within coming few decades, humans will soon be replaced by machines in every task. People will choose more and more capital intensive techniques. AI in layman language can be defined as origin of machines in performing these activities that were once performed by humans. With the help of robotics & AI, we can finish our work in less time and with little or no wastage. Every department of management i.e marketing department, finance department, R&D, production department, customer relationship building, customer support services etc, hold a good pace of AI into it. The work that was once performed by machines is now being replaced by robots and machines. This research study is based on experimental research & descriptive design both. Data collected is both primary and secondary. Primary data is collected by questionnaire method from 60 people of different age groups and secondary data is collected from various journals, fellow researcher papers, own publications, surveys by different organizations, reports of organization, etc. This paper reveals how much people are aware of AI, acceptance of AI by people, replacement of humans by machines & encourages the maximum use of AI and technology into management & customer support services.